The finite-difference time-domain method for electromagnetics with MATLAB simulations - Elsherbeni, Atef Z.; Demir, Veysel 1974- (SciTech Publishing, 2015)
The book contains 16 chapters containing following topics: nonuniform grid; graphics processing unit acceleration; dispersive material modeling; periodic structure analysis; total field formulation; scattered field formulation; thin-wire modeling; near-field to far-field transformation; advanced PML formulation; perfectly matched layer absorbing boundary; S-parameter; source waveform; time to frequency domain transformation; passive lumped element; active lumped element; finite-difference time-domain method; numerical stability; numerical dispersion and Yee grid.